Influence of the Frequency-chirp Gaussian Pulse on the Pulse Broadening in the Dispersive Fibers - Kien, Bui Xuan; Hung, Tran Hai; Chien, Trinh Dinh (Communications in Physics, 2013)
A signal optical pulse propagating in the fiber is affected by many factors, one of the most important among them is dispersion. Under the dispersive influence, the optical pulse is reshaped, particulally, its duration is changed. Especially, the pulse duration change of the optical short pulse with the frequency-chirp is unregular. It influences to the propagating distance in the fiber optic network. In this paper, the expression of the signal optical pulse with the frequency-chirp propagated through the dispersive fiber is derived. This expression described the broadening of the pulse in propagating process (broadening factor), which depends on the frequence chirp and dispersive parameters. The influence of those parameters on the pulse broadening is simulated and discussed.